5(x-3)=-(15-5x)

Simple and best practice solution for 5(x-3)=-(15-5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)=-(15-5x) equation:


Simplifying
5(x + -3) = -1(15 + -5x)

Reorder the terms:
5(-3 + x) = -1(15 + -5x)
(-3 * 5 + x * 5) = -1(15 + -5x)
(-15 + 5x) = -1(15 + -5x)
-15 + 5x = (15 * -1 + -5x * -1)
-15 + 5x = (-15 + 5x)

Add '15' to each side of the equation.
-15 + 15 + 5x = -15 + 15 + 5x

Combine like terms: -15 + 15 = 0
0 + 5x = -15 + 15 + 5x
5x = -15 + 15 + 5x

Combine like terms: -15 + 15 = 0
5x = 0 + 5x
5x = 5x

Add '-5x' to each side of the equation.
5x + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -68+4x+3x=114 | | 5x/2=-3x+11 | | 5p-2(4-2p)=19 | | Y=-2+-0.6666666667x | | -3/7w=9 | | 2x-(2-x)=13 | | x=(2m-4)/(1+n) | | 125^-2/3 | | 7x^2+40x+25=0 | | 9x-8x-10=13 | | 9.05=8.2 | | 3[8y+2]=10y+2[7y+3] | | 5/12=6/x | | 9+9-1-2+5m-1-4m=32 | | t*5=54 | | 3x-(5+2x)= | | x+4x-73=72 | | 10/3x2/5 | | 5x+16=2X | | 6x/3-18 | | 3/10(220) | | 2-3t+6+4t-12=9t | | 3c+8=5c+11 | | 2n+8=17 | | 555,555,555+124,135,352,246= | | 3Q-1+10-4+1-1-2=20 | | (1/3)*3(1/4) | | f(2)=3(2) | | 3.50t+5.50=51 | | -7n+10=4n+10 | | 3.60.+s=3 | | (3/5*x)-(2/3)=1 |

Equations solver categories